Analisis Stabilitas Pada Struktur Penahan Tanah (Studi Kasus Pantai Punaga Kabupaten Takalar) - Mustazim; Afdaliah, Athira; Syamsuri, Andi Makbul; Kasmawati (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Punaga Beach which located in Takalar Regency is frequently visited by tourists because it has a beautiful panorama. However, this tourist attraction also has problems that highly need attention. In certain seasons, this beach experiences increasingly severe coastal erosion problems due to strong waves and ocean currents. The impact of high tides that occur in several places causes coastal erosion and nearly damage the buildings. The purpose of this study was to determine the characteristics that occur at Punaga Beach and the effect of these characteristics on the stability of the revetment structure. This research was conducted at Punaga Beach, Mangarabombang District, Takalar Regency, South Sulawesi. The results of this study obtained the highest wave in 2022 was about 3.5 m and the toe protection stability value was obtained about 0.480. Therefore the toe protection stability number was about 90.5 which can be able to protect the revetment building from collapse